Anthocyanins of Coloured Wheat Genotypes in Specific Response to SalStress - Sonia Mbarki; Oksana Sytar; Marek Zivcak; Chedly Abdelly; Artemio Cerda; Marian Brestic (Molecules, 2018)
The present study investigated the effect of salt stress on the development of adaptive responses and growth parameters of different coloured wheat genotypes. The different coloured wheat genotypes have revealed variation in the anthocyanin content, which may affect the development of adaptive responses under increasing salinity stress. In the early stage of treatment with salt at a lower NaCl concentration (100 mM), anthocyanins and proline accumulate, which shows rapid development of the stress reaction. A dose-dependent increase in flavonol content was observed for wheat genotypes with more intense purple-blue pigmentation after treatment with 150 mM and 200 mM NaCl. The content of Na+ and K+ obtained at different levels of salinity based on dry weight (DW) was more than 3 times greater than the control, with a significant increase of both ions under salt stress. Overall, our results demonstrated that coloured wheat genotypes with high anthocyanin content are able to maintain significantly higher dry matter production after salt stress treatment.